Investigating Water-Energy-Food Nexus in the Production of Summer Agricultural Products in Dehloran County - Ehsan Bahmani; Ali Asghar Mirakzadeh; Shahpar Geravandi; Faranak Karamiyan (آب و توسعه پایدار)
An integrated perspective between the three sources of water, energy, and food is necessary for agricultural management and policies adapted to climate change in order to prevent anomalies and promote sustainable development. The goal of this study was to examine how Dehloran county's four summer agricultural products—watermelon, sesame, mung, and maize—are produced in relation to the water-energy-food nexus. Farmers were given a questionnaire to complete in order to obtain the necessary data. The questions focused on water and energy consumption, physical and economic energy efficiency, and, lastly, the water-energy-food correlation index (WEFNI) for each product. The findings indicated that the production of summer crops in Dehloran City uses 1167.14 m3.ha-1 of water; watermelon (7641 m3.ha-1) and sesame (994 m3.ha-1) had the highest and lowest respective water consumption. The total energy used in product cultivation was 205093 MJ.ha-1. Maize (103558.85 MJ.ha-1) and sesame (17306.73 MJ.ha-1) had the highest and lowest input energy consumption, respectively. Additionally, the two energy-intensive industries in the agriculture sector are electricity and chemical fertilizers. According to the data, sesame had the highest economic productivity of water (297000Rls.m-3) and energy (17050Rls.MJ-1), while watermelon had the highest physical productivity (6.67 Kg.m-3) and energy (0.90 Kg.MJ-1). The most sustainable product in terms of resource consumption was watermelon (WEFNI = 0.71), while the least stable product was mung beans (WEFNI = 0.035), according to correlation index values. The outcomes of this study can support the region's agricultural industry's sustainable growth by implementing appropriate resource management practices and cultivation patterns.